Application of heterocyclic aldehydes as components in Ugi–Smiles couplings - Mason, Katelynn M.; Meyers, Michael S.; Fox, Abbie M.; Luesse, Sarah B. (Beilstein Journal of Organic Chemistry, 2016)
Efficient one-pot Ugi–Smiles couplings are reported for the use of furyl-substituted aldehyde components. In the presence of these heterocyclic aldehydes, reactions tolerated variations in amine components and led to either isolated N-arylamide Ugi–Smiles adducts or N-arylepoxyisoindolines, products of tandem Ugi–Smiles Diels–Alder cyclizations, in moderate yields. A thienyl-substituted aldehyde was also a competent component for Ugi–Smiles adduct formation.
Keywords: Diels–Alder cycloaddition; epoxyisoindoline; multicomponent coupling reaction; tandem reaction; Ugi–Smiles coupling